Pengaruh Sosial Media Dan Celebrity Endorser Terhadap Keputusan Pembelian Produk Inspired (Studi Kasus Pada Mahasiswa Universitas Islam Malang Angkatan 2020) - Aulia, Nadhira Saffana; Rachma, N.; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Current industrial development is very dependent on company efficiency and utilizing developments in digital technology for business growth and development. These business developments can also be accessed by the public via the website provided. Quantitative analysis methods are modern business and scientific research. Quantitative research methods use quantitative methods that utilize information, namely research methods that are based on positivistic (concrete data), research data in the form of numbers that will be measured using statistics as a calculation test tool. Social Media and Celebrity Endorsers have a simultaneous influence on student product purchasing decisions. Islamic University of Malang class of 2020. This shows that Inspired products can make decisions to buy their products because of Social Media which attracts consumer attention, and has celebrities to promote the product.  Keywords: Social Media, Celebrity Endorsers, Buying Decision